Religion lesson in schools in Poland – the subject of dispute and the unused potential - Horowski, Jarosław (British Journal of religious education, 2022)
The aim of this article is to examine lessons on religion in Poland from the perspective of the prevailing legal, social, cultural, and organisational conditions, as well as to look at the research that has already been devoted to this topic. In the first part, the religious context specific to Poland, based on level of declared religious identity which leads to a clear domination of Catholics over representatives of other religions and denominations, is discussed. The rules underlying the organisation of the teaching of religion as defined in law are also presented in this section. In Poland, where religion lessons are of a confessional nature, the decision about students’ participation must be made by parents, or by the students if they are adults. In the second part of the text, research specific to religious education in schools is presented. In Poland, this subject is approached primarily from a philosophical and theological perspective, as teachers of religion are trained in theological faculties. Consequently, as part of a general reflection on religious education, personalistic thought is developed (and especially the pedagogy of the person). An ongoing opposition to confessional religious lessons, resulting from secularisation processes, has also led to concepts of school religious education being built on assumptions of critical theory. However, little empirical research on religion lessons in Poland has been conducted to date, especially few studies in which the balance between the religious development of students and their functioning in social relations and culture has been assumed.